Vegetative Compatibility Groups within Fusarium oxysporum f. sp. cepae in Hokkaido-Japan - . WIDODO; NORIO KONDO; KIROKU KOBAYASHI; AKIRA OGOSHI (Indonesian Society for microbiology, 2008)
In Hokkaido, Fusarium basal rot, caused by Fusarium oxysporum f. sp. cepae is one of the important constrains since 1973 which contributes to a significant loss in onion production, either in the fields or during storage. Development of resistant cultivars is suggested as one of the effective control measures against the disease, however, this should be accompanied with thebetter understanding of the pathogen’s population dynamics. This study was performed to investigate the population structure of F. oxysporum f. sp. cepae based on vegetative compatibility groupings (VCGs). Vegetative compatibility groups of F.oxysporum f. sp. cepae were characterized using nitrate non-utilizing (nit) mutants. Four VCGs and 2 single self-compatible (SSC) isolates were identified among 48 isolates, designated as VCG 0420 (33 isolates), 0421 (9 isolates), 0422 (2 isolates), 0423 (2 isolates), and 042-(2 isolates). VCG 0420, to which 4 ATCC isolates out of 6 belonged, was the predominant group within the growing region encompassing Hokkaido Japan. VCGs 0421 and artificial VCG 042- were found less frequently. Four isolates from Welsh onion were not compatible with any recovered VCGs and were assigned to 2 distinct VCGs (VCG 0422 and 0423).